2017
DOI: 10.1159/000475659
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of <b><i>Helicobacter pylori</i></b> Infection in Japanese Hemodialysis Patients

Abstract: Introduction:Helicobacter pylori (H. pylori) infection is one of the major risk factors for gastrointestinal morbidity in hemodialysis patients. Primary end point is to investigate H. pylori infection rate in hemodialysis patients. As secondary end point, we clarified whether pepsinogen (PG) level was related with H. pylori infection status in hemodialysis patients. Methods: Serum levels of PG I, II, and anti-H. pylori IgG antibody were assessed in 500 Japanese hemodialysis patients. Results:H. pylori infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Decrease of PG I and PG I/II ratio is associated with gastric atrophy. We confirmed that PG I and II were useful in HD patients in our previous study .…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Decrease of PG I and PG I/II ratio is associated with gastric atrophy. We confirmed that PG I and II were useful in HD patients in our previous study .…”
Section: Methodssupporting
confidence: 89%
“…Measurement of serum PG level is useful for the detection of gastric mucosal atrophy, especially in gastric corpus, and has been used as a screening method for gastric cancer and risk assessment. Although serum PG level is elevated in patients with renal failure due to decreased renal clearance of PG, our previous studies suggested that PG I and II levels and PG I/II ratio decreased according to the severity of gastric atrophy, and PG I/II ratio higher than 7.75 might predict H. pylori negativity in HD patients . In general, the prevalence of gastric atrophy increases with advancing age and is similar between men and women .…”
Section: Discussionmentioning
confidence: 87%
“…A large-scale Japanese epidemiological study showed that the infection rate in Japanese has declined to 30%-50%, especially in younger patients[ 26 ]. Supporting this phenomenon, an investigation of 500 Japanese HD patients with a mean treatment duration of 6.9 ± 6.6 years (2015) reported that the prevalence of infection had dramatically decreased, to 15.0% (95%CI: 12.0-18.4)[ 27 ]. Although it has not yet been proven, decreasing rates of H. pylori infection suggest that the incidence of peptic ulcer disease and gastric cancer is expected to be decreasing in HD patients and that QOL in HD patients has improved due to decreases in H. pylori- related gastrointestinal disease.…”
Section: H Pylori Infection In Hd Patientsmentioning
confidence: 99%
“…There is an inverse relationship between H. pylori infection and dialysis treatment duration (Table 1 )[ 20 , 27 - 31 ]. We showed that the duration of HD treatment in H. pylori- positive patients was 4.6 ± 3.8 years, which is significantly shorter than that in H. pylori- negatives (7.3 ± 6.9 years, P = 0.001)[ 27 ].…”
Section: Treatment Periods Of Hd and H Pylori Infmentioning
confidence: 99%
See 1 more Smart Citation